Word-initial h aspiration and the presence of the post-velar fricative [χ] in New Mexico Spanish - Donny Vigil (Estudios de Fonética Experimental, 2018)
Researchers first reported the aspiration of word-initial orthographic h (i.e. humo [ˈhu.mo]) in the traditional Spanish of New Mexico over a century ago. Subsequent studies confirmed the presence of this aspiration, but, to date, none have gone into phonetic and spectrographic detail. The current study summarizes some of the synchronic reports of h aspiration, details diachronic explanations given, as well as provides spectrographic analyses of this phenomenon as produced by six speakers of traditional New Mexico Spanish in a guided elicitation speech task. The results reveal that word-initial h aspiration is not only realized as both a glottal fricative [h] and a voiceless velar fricative [x] as previously reported, but also as a voiceless post-velar fricative [χ].